(untitled) (Bangladesh Journal of Agricultural Research, 2010)
An experiment was conducted to study the in vitro culture of pointed gourd. Cotyledon rescued from physiologically matured seeds (PMS) and immatured seeds (IMS) of pointed gourd were used as explants. Cotyledon excised from PMS responded very well in all culture conditions. Plant regenerated from cotyledon of PMS ranged from 38 to 96% in different hormonal formulations of culture media. Highest percentage of shoot regeneration was observed in MS + 1.0 mg/l BAP and lowest in MS + 2.5 mg/l BAP. No plant regeneration was observed in cotyledon from immatured seeds. The highest percentage of root induction (99%) was achieved in half MS medium supplemented with 0.5 mg/l NAA. The regenerated plantlets were successfully established in earthen pot. Keywords: Cotyledon; in vitro; pointed gourd. DOI: 10.3329/bjar.v35i1.5874 Bangladesh J. Agril. Res. 35(1) : 135-142, March 2010